Variations in Superficial Palmar Arch: Case Series with Clinico-anatomical Perspective - Dibakar BORTHAKUR; Rajesh KUMAR; Seema SINGH (Medeniyet Medical Journal)
The superficial palmar arch (SPA) is an important anastomotic network primarily formed by the superficial branch of the ulnar artery with one of the superficial branches of the radial artery. SPA variations were observed in three out of 20 cadaveric hand specimens. Two cases of unilateral incomplete SPA and the third case of a unilateral ulnar-to-median complete SPA were recorded. The incomplete SPA was located superficial to the flexor digitorum tendons and deep to the palmar aponeurosis. SPA in the remaining 17 hands was anatomically normal, with major contributions from the superficial palmar branch of the ulnar artery and minor contributions from the superficial palmar branch of the radial artery. These variations are clinically important, especially during procedures like arterial blood sampling, cardiac catheterization, and hemodialysis. Thus, anatomical variabilities in this region may cause complications with vascular occlusion if not ascertained before the procedure.